Synthesis and characterisation of calcium sulfoaluminate cements produced by different chemical gypsums. Issue 3 (31st January 2018) - Telesca, Antonio; Marroccoli, Milena; Winnefeld, Frank
Abstract : Calcium sulfoaluminate (CSA) cements show some desirable environmentally friendly features which include the possibility of using several industrial by-products as raw materials in their manufacturing process. Four chemical gypsums (flue-gas desulfurisation gypsum, fluorogypsum, phosphogypsum and titanogypsum) have proved to be suitable as total substitutes for natural gypsum (NG) in the raw meal. Mixtures based on limestone, bauxite, NG or one of the CS ¯ -rich by-products were heated in a laboratory electric oven from 1150 to 1300°C. The reactivity of raw mixtures to form clinker products was evaluated using X-ray diffraction (XRD) analysis. The raw mixtures containing industrial gypsum displayed better reactivity towards C4 A3 S ¯ than the one made with NG. Moreover, conduction calorimetric measurements associated with XRD and differential thermal-thermogravimetric analyses showed that all CSA cements, obtained by adding commercial anhydrite to clinkers produced at the optimum synthesis temperatures, have similar hydration products but with different hydration kinetics.